ANALIZA INVESTICIJA KAO DETERMINANTI PRIVREDNOG RASTA REPUBLIKE SRBIJE U KONTEKSTU PRIBLIŽAVANJA EVROPSKOJ UNIJI - Đurić, Dejan; Stankov, Biljana; Roganović, Milijana (International Journal of Economic Practice and Policy, 2022)
Intensifying investment activities, strengthening the institutional sector and improving the competitiveness of the national economy stand out as the most important goals of the economic policy of the Republic of Serbia for proceeding with European integration. In this regard, the main goal of this paper is the analysis of investments as one of the most important determinants of economic growth of the Republic of Serbia in the process of accessing the European Union. Given the fact that the Republic of Serbia, as a candidate for membership in the European Union, has been constantly working on harmonizing its legal, institutional and other pillars with the acquis communautaire, research on this topic has gained special significance. The European Union representthe most important investment partner of the Republic of Serbia, especially in terms of foreign direct investment inflows, as well as one of the leading creators of new jobs in the trade sector. The authors of the paper will pay special attention to the current trends and the achieved level of investments in the Republic of Serbia, as well as to their impact on the dynamics of economic growth. The paper will examine the importance of improving the competitiveness of the economic environment as well as the need to accelerate the process of European integration in order to solve the problem of slow economic growth of the Republic of Serbia and intensify investment inflows in the future.
Keywords: investment; economic growth; Republic of Serbia; European Union